Excavations at Nimrud (Kalḫu), 1955 - Mallowan, M. E. L.
Progress and Scope of the 1955 Excavations — Nabu Temple and South East Building — S. E. Building: The Throne-Room — Stratigraphie Observations at the S. E. End of the Mound; Their Relevance for the Dating of the Ivories — Correlation of Levels in the Stratigraphic Sequences with Historical Sequences at Nimrud.